The Effect of Improvement Surrounding Soil on Driven Pile Friction Capacity - Aziz, Abdulaziz Abdul Rassol; Salman, Mohammed M. (Al-Nahrain Journal for Engineering Sciences, 2017)
There is very close relation between the pile capacity and surrounding soil conditions . In cohesionless soil the pile effected on surround soil by compact loose ,cohesionless deposits through a combination of pile volume displacement and driving vibrations .the pile foundation usually designed to exceed the weak soil to the firm deposit .in this study we shall try to improve the weak soil surround the pile and observe the effect of improvement on pile capacity for driven pile._x000D_ The improvement suggested in this study is compacting for surrounding soil . for this purpose we prepare testing program by selection two types of sand soil one as the origin soil and the other as improving soil (soil will be compacted and replace surround pile model) . pile model prepared for this purpose is consist of reinforcement steel bar covered with cement mortar , 50 kN automatic electromechanical compression machine was used for testing load- settlement test on pile model. The Testing procedure includes changing the diameter of soil compacted around pile model and execute the load settlement test and compare the results.